Antimicrobial Prescription Pattern in Ho Teaching Hospital, Ghana: Seasonal Determination Using a Point Prevalence Survey - Cornelius C. Dodoo; Emmanuel Orman; Thelma Alalbila; Adelaide Mensah; Jonathan Jato; Kwadwo A. Mfoafo; Isaac Folitse; Araba Hutton-Nyameaye; Inemesit Okon Ben; Paapa Mensah-Kane; Emmanuel Sarkodie; Eneyi Kpokiri; et al. (MDPI AG, 2021)
A standardised Global Point Prevalence Survey (PPS) tool was used to determine the antimicrobial prescription pattern in the Ho Teaching Hospital on two separate occasions in a total of 14 wards in the hospital, including dedicated wards for paediatrics and neonates. Manually collected and anonymised data were entered, validated, analysed and reported using a web-based global PPS application. With 147 and 153 patients considered in the July 2019 and January 2020 surveys, respectively, 98 patients (66.7%) and 84 patients (54.9%) had received one or more antimicrobials. The prevalence of antimicrobial use in the adult wards was 64.3% (72/112) and 53.4% (63/118) in the first and second surveys, respectively. The prevalence in the paediatric wards was 60.0% (12/20) and 62.5% (10/16), respectively, in the two surveys, while that in the neonatal wards was 93.3% (14/15) and 57.9% (11/19), respectively. β-lactams were the most used antibiotics in both periods. Malaria was the most common diagnosis requiring the use of antimicrobials in July 2019, accounting for 19.4% of the diagnoses, whereas in January 2020, it was skin and soft-tissue conditions (28.1%). This reflects a seasonal association between malaria and rainfall patterns. Out of the antimicrobials prescribed during each of the survey periods, 95% were used for empirical treatment, and this could be attributed to a number of reasons, including logistical challenges, among others, that require further exploration in the context of local, national and international policy recommendations.